2021
DOI: 10.1111/jcmm.16191
|View full text |Cite|
|
Sign up to set email alerts
|

M2 macrophage‐derived G‐CSF promotes trophoblasts EMT, invasion and migration via activating PI3K/Akt/Erk1/2 pathway to mediate normal pregnancy

Abstract: Trophoblasts are important parts of the placenta and exert vital roles in the maternal‐foetal crosstalk, and sufficient trophoblasts migration and invasion is critical for embryo implantation and normal pregnancy. Macrophages, as the major components of decidual microenvironment at maternal‐foetal interface, can interact with trophoblasts to participate in the regulation of normal pregnancy. Previously, our group have demonstrated that trophoblasts could induce macrophages polarization to M2 subtype by secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 50 publications
3
45
0
Order By: Relevance
“…The association between the overexpression of NLRP3 in ammasomes and RSA had been con rmed, which was consistent with our experimental results [6,28]. Therefore, we believe that the loss of G-CSF, on the one hand, disrupts the function of trophoblasts, and on the other hand, interferes with the pro-in ammatory and anti-in ammatory balance at the mother-foetal interface through macrophages, which in turn leads to impaired trophoblasts function [7,29] and ultimately induces RSA.…”
Section: Discussionsupporting
confidence: 91%
“…The association between the overexpression of NLRP3 in ammasomes and RSA had been con rmed, which was consistent with our experimental results [6,28]. Therefore, we believe that the loss of G-CSF, on the one hand, disrupts the function of trophoblasts, and on the other hand, interferes with the pro-in ammatory and anti-in ammatory balance at the mother-foetal interface through macrophages, which in turn leads to impaired trophoblasts function [7,29] and ultimately induces RSA.…”
Section: Discussionsupporting
confidence: 91%
“…Then they begin to transition to a mixed M1/M2 profile when the trophoblasts establish attachment into the endometrium and invade the uterine stroma. In general, decidual macrophages are characterized by an immunosuppressive phenotype as M2 polarization secreting IL-10, TGF-β, and G-CSF, supporting fetal-maternal immune tolerance during implantation ( 45 , 46 ). Abnormal macrophage polarization is related to many pregnancy complications, such as PE, premature birth, and RM ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although it was found that dMϕ had no effect on the invasion of primary EVTs ( 37 ), it was also reported that LPS-stimulated peripheral blood monocytes could inhibit HTR-8/SVneo cell invasion by the secretion of TNFα ( 38 ), and M2 macrophages showed an enhanced promotion effect on trophoblast cell motility ( 39 ); these suggest that the dMϕ might inhibit EVTs invasion in early pregnancy. However, in this study, we found that the dMϕ from normal women in early pregnancy exerted a stimulatory effect on HTR-8/SVneo cell motility ( Figure 4C ).…”
Section: Discussionmentioning
confidence: 99%